The Role of the Health Department in Stunting Prevention in Muaro Jambi Regency - Syafriana Syafriana (Budapest International Research and Critics University, 2022)
The government has set a target of reducing stunting in 2024 to 14%. On August 9, 2017 at a follow-up Ministerial Meeting, the Vice President decided on the Five Pillars of Stunting Prevention by implementing convergence (Ministry of Health of the Republic of Indonesia, 2021). This study aims to determine the role of the Muaro Jambi District Health Office in preventing stunting. The method in this research is qualitative, by conducting in-depth interviews with informants (Indeph interviews). The informants in this study were the head of the health office, the secretary of the district health office and the head of family health at the muaro jambi district health office as well as several heads of public health centers and the person in charge of the stunting program at the health center in the muaro jambi district. The conclusion of this study is that the role of the Health Office greatly influences the achievement of stunting reduction activities because the health department is the OPD that directly implements the recovery program (Sensitive Nutrition and Specific Nutrition) through the puskesmas. For the implementation of stunting reduction and prevention, it is necessary to plan activities to be carried out so that it requires funding that is supported by the local government. This stunting prevention activity is carried out continuously, not only when the stunting locus occurs, but on an ongoing basis so that the role of the health department in monitoring the results of activities carried out by the puskesmas continues to be carried out. The health department's programs in the context of prevention can continue to be implemented, such as giving PMT to infants and toddlers as well as pregnant women.